Pengembangan Soal Numerasi berorientasi AKM berbasis Cagar Budaya Kota Bengkulu untuk Siswa Kelas V Sekolah Dasar - Vivi Oktavia; Agus Susanta; Bambang Parmadi (UNIB Press, 2024)
The results of the numeracy skills of fifth grade elementary school students based on the National Assessment are still low and students do not fully understand how to do numeracy questions. This research aims to develop numeracy questions oriented to the Minimum Competency Assessment based on the cultural heritage of Bengkulu City to prepare fifth grade elementary school students for the National Computer-Based Assessment. The type of research used is research and development of the ADDIE model. The results of the research show that the numeracy questions oriented to the Minimum Competency Assessment based on the cultural heritage of Bengkulu City are logically, empirically and practically feasible. The student ability profile based on the percentage of achievement in the number domain was 70.27%, the geometry and measurement domain was 86.39%, the data and uncertainty domain was 85.83%, and the algebra domain was 80.56%. Based on the results of research and development, it was concluded that the numeration questions oriented to the Minimum Competency Assessment based on the cultural heritage of Bengkulu City for fifth grade elementary school students were very feasible and effective to use to help prepare for the National Computer Based Assessment on numeracy topics at the elementary school level.